2015
DOI: 10.1039/c5ra13377g
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two new nitrogen-rich tetrazine derivatives as high performance and safe energetic compounds

Abstract: This work introduces two novel nitrogen-rich derivatives of tetrazine, i.e. 1,2-bis (6-nitro-1,2,4,5tetrazin-3-yl) diazene and 1,2-bis(6-nitro-1,2,4,5-tetrazin-3-yl)hydrazine, as high performance and safe energetic compounds. Reliable methods are used to study physical, thermodynamic, sensitivity, detonation and combustion properties of these compounds, which include crystal density, condensed phase heat of formation, impact sensitivity, electric spark sensitivity, heat of detonation, detonation temperature, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…1,2,4,5-tetrazine, as one of the promising nitrogen rich [6][7][8][9][10][11][12] EMs, has a nitrogen content of 68.3% in the six-member ring, which makes them present high density and easily obtain oxygen balance, furthermore, the main combustion product is clean gas N 2 [13]. Therefore, they are considered as green energetic materials used in solid propellants, explosives, and civil combustible gas generators [6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,5-tetrazine, as one of the promising nitrogen rich [6][7][8][9][10][11][12] EMs, has a nitrogen content of 68.3% in the six-member ring, which makes them present high density and easily obtain oxygen balance, furthermore, the main combustion product is clean gas N 2 [13]. Therefore, they are considered as green energetic materials used in solid propellants, explosives, and civil combustible gas generators [6].…”
Section: Introductionmentioning
confidence: 99%
“…V M is the volume inside the 0.001 a.u. isosurface of electron density surrounding the molecule calculated using DFT at the B3LYP/6-31G(d,p) with the Gaussian program package [19]. The calculated densities of the compounds are mentioned in Table 1.…”
Section: Crystal Densitymentioning
confidence: 99%
“…It was indicated that suitable DFT and empirical methods can be used to obtain different properties [18][19][20][21]. The purpose of the presented work is to introduce five high performance derivatives of tetrazole ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Since energetic derivatives of nitrogen-rich heterocyclic materials have usually more than 50 wt.% nitrogen, they are called high nitrogen content (HNC) materials [4]. Different predictive methods can be used to design high-performance HNC explosives with desirable physicothermal, detonation and combustion properties as well as low sensitivities [3,[5][6][7][8][9][10][11]. Due to the importance of the condensed phase heats of formation of HNCs, several methods, including group additivities and quantitative structure-property relationships (QSPR), have been used in recent years [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%